Luminescent Properties of Composite Systems Based on Polystyrene and Erbium(III) Phthalocyaninates in Near IR Spectral Region - Belogorokhov, I.A.; Belogorokhova, L.I.; Ryabchikov, Yu.V.; Pushkarev, V.E. (Biomedical Chemistry: Research and Methods, 2018)
Composite materials based on polystyrene and ErIII phthalocyaninates of single-, double- and triple-decker structure were obtained, and their spectral luminescent characteristics in the near-IR (NIR) range were studied. All the ErIII complexes in these composites reveal 4f photoluminescence (PL), which is observed at 1550 nm for mono- and tris(phthalocyaninate), whereas in the case of bis(phthalocyaninate), the PL maximum is shifted to the short-wavelength region and appears at 1440 nm. A comparative analysis of the properties of composites and individual phthalocyanine compounds in films and solutions was carried out. In the case of a single-decker complex, this emission was detected for the first time in the polystyrene matrix, while for individual ErIII mono(phthalocyaninates), this process was not observed earlier.